Legibility in the Age of Signs and Machines - Hesselberth, Pepita; Houwen, Janna; Peeren, Esther; de Vos, Ruby (Thamyris/intersecting : place, sex and race, 2018)
This volume reflects on what legibility entails in today's machinic world. It asks what makes cultural expressions, from literary texts, films, artworks and museum exhibits to archives, laws and algorithms, il/legible to whom or what, and with what consequences.